Who is behind the sustainable purchase? The sustainable consumer profile in grocery shopping in Spain. (16th June 2016) - Carrero, Isabel; Redondo, Raquel; Fabra, Maria Eugenia
Abstract: Studies of sustainable consumer profiles are mainly label‐specific and focus on Organic or Fair Trade labels. As a result, when the sustainable consumer is defined, there is a sense that only one profile exists. If each label has a different positioning strategy and has different requirements, the buyers of these products may also be different. Through the use of consumer panel data, this paper aims to deepen the understanding of the household demographic profiles of consumers of sustainable brands in order to discover if there is a single sustainable consumer profile or whether there is diversity associated with different labels. This study reveals profile differences and these provide better understanding of the complexities of sustainable consumption. It reveals that the profiles of sustainable buyers are not the same across all labels and this should be taken into account by awarding institutions when designing and evaluating their positioning strategies.